A impressão da não-linearidade temporal no filme "A Chegada": uma análise da montagem enquanto ferramenta de estruturação narrativa - Pinto, Rebeca Braga [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This research has as primary premises the cinema's ability to create impressions on the spectator and the processes of film editing as a tool for narrative structure, aiming for the goal to comprehend in which ways the editing process of the movie "Arrival" (2016) has added to the construction of the spectator impressions on temporal nonlinearity placed on it's narrative. In order to do that, firstly it was developed the concepts of film editing field, along with the conceptions that permeate a nonlinear storytelling, so that it was possible to attain a qualitative movie analysis and identify how the film editing process interferes with the spectator reception. Through the analysis of one of the final sequences of the movie, it was possible to verify that, even though the editing process being a resource that in general has to remain indistinguishable in the discursive axis, the part that it plays on the filmic speech is clear, it is a determining factor on the final conception of the product, in which acts on the empirical object as a tool of combinatorial articulation between the diegetic axis and the discursive axis of the movie, so that the temporal nonlinearity theory placed on the diegesis it's applied to the movie form itself, setting a metalinguistics reference and above all, meta-discursive, about the narrative temporal logic. Therefore, the sequence on the discursive axis transports to the spectator it's notion of nonlinear time (one without a beginning and an end defined) inserting them on the temporal experience by inducing their perception through the subjective relationship that is conceive when the chaining of the scenes is assimilated, establishing thus a nonlinear temporal impression.

Tendo como principais premissas a capacidade do cinema de criar impressões no espectador e a montagem enquanto ferramenta de estruturação narrativa, essa pesquisa apresenta como objetivo geral compreender de que forma e em quais âmbitos o processo de montagem do filme "A Chegada" (2016) contribuiu para a construção da impressão de não-linearidade temporal presente em sua narrativa; sendo que, para isso, foram primeiramente desenvolvidos os conceitos do campo da montagem e foram exploradas as concepções que permeiam uma narrativa cinematográfica não-linear, para que fosse possível então realizar uma análise fílmica qualitativa e identificar de que forma a montagem interfere na recepção do espectador. Através da análise feita sobre uma das sequências finais do filme, comparando a montagem com sua disposição no roteiro, foi possível constatar que, apesar da montagem em grandes partes precisar ser um recurso imperceptível no eixo discursivo, o papel que exerce na construção do discurso fílmico é nítido, trata-se de um fator determinante sobre a concepção do produto final; nesse sentido, esta atua no objeto empírico como uma ferramenta de articulação combinatória entre o eixo diegético e o eixo discursivo da obra, de forma que a teoria da não-linearidade temporal inerente a diegese é aplicada à própria forma do filme, configurando assim uma referência metalinguística e acima de tudo, meta-discursiva, a respeito da lógica temporal da narrativa. Assim sendo, a sequência no eixo discursivo transporta ao espectador a sua noção de tempo não-linear (sem um início e um fim determinados) sendo capaz de inseri-lo na experiência temporal ao provocar sua percepção por meio da relação de subjetividade que este concebe ao assimilar o encadeamento das diferentes cenas, estabelecendo assim a impressão da não-linearidade temporal.
The nonlinear temporal impression in the movie "Arrival": an analysis of film editing as a tool for cinematic narrative structure
Keywords: Movie theater; Motion picture film; Film editing; Cinematic narrative; Nonlinear storytelling; Arrival; Movie analysis; Cinema; Filme cinematográfico; Montagem cinematográfica; Narrativa cinematográfica; Não-linearidade narrativa; Análise fílmica; A Chegada